2020
DOI: 10.25259/sni_316_2020
|View full text |Cite
|
Sign up to set email alerts
|

Rare neurohypophyseal tumor presenting as giant pituitary macroadenoma with cavernous sinus invasion – A case report and review of literature

Abstract: Background: Granular cell tumors (GCTs) of the pituitary are rare tumors of posterior pituitary that can present as giant pituitary macroadenoma due to the slow indolent growth of the tumor. We are reporting this case due to the rarity of GCT and usually these tumors are confined to the suprasellar region since they are arising from the pituitary stalk. GCTs that attain such giant size with cavernous sinus invasion are still rarer. Case Description: A 38-year-old female who presented with progressive deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In clinical practice, PPTs are uncommon and are often misdiagnosed as pituitary adenomas or craniopharyngiomas before operation. Previous studies have suggested that PPTs are hypervascularized ( 3 , 4 ); thus, clinical suspicion of PPTs before surgery is a real challenge. Recent advances in endoscopic surgery have provided better illumination and close-up observation during transsphenoidal surgery ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, PPTs are uncommon and are often misdiagnosed as pituitary adenomas or craniopharyngiomas before operation. Previous studies have suggested that PPTs are hypervascularized ( 3 , 4 ); thus, clinical suspicion of PPTs before surgery is a real challenge. Recent advances in endoscopic surgery have provided better illumination and close-up observation during transsphenoidal surgery ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%